Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1985
DOI: 10.1056/nejm198504253121702
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Aerosolized Insulin

Abstract: We assessed the efficacy of intranasal aerosolized insulin containing laureth-9 as a surfactant in patients with Type I diabetes by fasting studies in 8 patients, mixed-meal studies in 15, and long-term home use in 8. The intranasal insulin (1 U per kilogram of body weight in 1 per cent laureth-9) was rapidly absorbed (in 15 minutes); it lowered the plasma glucose level by 50 per cent in 45 minutes in fasting normal controls and by 50 per cent in 120 minutes in fasting diabetics. The glucose-lowering potency d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Chiou et al 3 showed no irritation in the peripheral tissue of eye due to 50 µL of 0.25% insulin eyedrops containing 0.5% of Brij-78. In addition, Salzman et al 21 pointed out that 0.1% laureth-9 (polyoxyethylene-9 lauryl ether) in intranasal spray insulin was completely tolerated in all of the study subjects. On the other hand, some preliminary studies 22,23 regarding insulin intranasal systemic delivery have indicated that the absorption enhancer will irritate the nasal mucosa.…”
Section: Discussionmentioning
confidence: 95%
“…Chiou et al 3 showed no irritation in the peripheral tissue of eye due to 50 µL of 0.25% insulin eyedrops containing 0.5% of Brij-78. In addition, Salzman et al 21 pointed out that 0.1% laureth-9 (polyoxyethylene-9 lauryl ether) in intranasal spray insulin was completely tolerated in all of the study subjects. On the other hand, some preliminary studies 22,23 regarding insulin intranasal systemic delivery have indicated that the absorption enhancer will irritate the nasal mucosa.…”
Section: Discussionmentioning
confidence: 95%
“…Nonetheless, nasal insulin delivery can be achieved through the use of absorption enhancers at a bioavailability similar to that recorded for pulmonary delivery (*5-10%). 201,202 These additives, which include such entities as phosphotidylcholine derivatives, 203 laureth-9, 204 and bile salts, 205 have been associated with acute and chronic nasal irritation. Finding the right combination of insulin and absorption enhancer that provides efficacy with little adverse effect remains the central challenge for this route of administration.…”
Section: Nasalmentioning
confidence: 99%
“…In contrast to our study, earlier investigations on intrapulmonary and intranasal insulin administration have not been randomized, nor blinded and the materials have also been fairly small with as few as six subjects receiving treatment on only one occasion [10,11], except for Salzman et al who investigated a total of 45 patients with insulindependent diabetes mellitus (IDDM) [12].…”
Section: Discussionmentioning
confidence: 72%